"Multiple Papillomas - a case report and review of literature" - Gaurav Sharma; Archana Nagpal; Manoj Vengal; Keerthilatha M Pai (Wolters Kluwer Medknow Publications, 2007)
We report a unique case of extensive papilIomatosis of the left buccal mucosa in an 80 year old female patient. We document and discuss the probable multifactorial etiology of the lesions and the possible involvement of a syndromic association. This report illustrates the need for careful clinical investigation and follow-up of individuals presenting with multifocal involvement of papillomas.